Developing a CTG simulator app: theory and practice. (3rd November 2015) - Ford, Jessica; Langley, Catherine; Molyneux, Adrian; Shelton, Clifford
Summary: Background: Cardiotocograph (CTG) interpretation is a core skill for health care professionals working on the labour ward; however, training appears to be deficient in respect of the development of decision‐making skills relating to CTG findings. Simulation offers a potential solution to address such 'human factors'. Current access to simulators is limited by cost and operational complexity. We therefore decided to develop an accessible CTG simulator application ('app') that could be operated on a smartphone, a technology already possessed by the majority of health care professionals in the UK and elsewhere. CTG interpretation is a core skill for health care professionals working on the labour ward Context: A multidisciplinary team with backgrounds in obstetrics, anaesthesia and information technology was assembled to undertake the software development process. An evaluation of the pilot software was undertaken by trainee obstetric doctors. Innovation: A software development project was undertaken in order to produce a mobile app that simulates CTG accurately and dynamically. This process was based on Davis' Technology Acceptance Model, in which usefulness and ease of use are the central principles. Implications: Mobile technology can be used to run simulation software that is both useful and easy to use; however, our evaluation indicated that in order to use the app effectively the operator requires some expertise in the behaviour of the CTG in response to interventions, in common with all current patient simulators. We envisage using this app in hybrid simulation scenarios, in which a live actor and a simulated monitor are used together.